Peran Self-Esteem Terhadap Psychological Well-being Remaja Korban Bullying - Fatin Lu’lu’ Urrohmi; Triantoro Safaria (Universitas Kristen Maranatha, 2025)
The objective of this study was to examine the role of self-esteem in predicting the psychological well-being of adolescent victims of bullying. This research employed a quantitative approach with a cross-sectional design. The participants were adolescent bullying victims recruited through purposive sampling, with inclusion criteria specifying adolescents aged 13 to 17 years who had experienced bullying. A total of 319 participants were involved in the study. The proposed hypothesis stated that self-esteem would positively predict psychological well-being. Data were collected using Ryff’s Psychological Well-Being Scale and the Rosenberg Self-Esteem Scale. Content validity estimation, Cronbach’s alpha reliability testing, and multiple regression analysis were conducted using SPSS version 25 for Mac. Results of the multiple linear regression analysis indicated a significant effect, F(1, 318) = 7.642, p = .006, showing that self-esteem accounted for 5% of the variance in psychological well-being. These findings demonstrate that self-esteem plays a positive role in the psychological well-being of adolescent bullying victims. Future studies are recommended to investigate additional variables that may influence psychological well-being among this population.